Perlindungan Hukum terhadap Anak yang Melakukan Tindak Pidana Pencabulan pada Putusan No.2/pid.sus/2014PN.Mdn - Sidabutar, Risna; Suhatrizal, Suhatrizal (Jurnal Ilmiah Penegakan Hukum, 2018)
Legal Protection for Children Conducting Crimes of Harassment on Decision No.2 / pid.sus / 2014PN.Mdn Legal protection, for children can be interpreted as an effort to protect the law on various rights and freedoms of children and various interests related to child welfare. So, all children are protected, including children who are dealing with the law (ABH). The purpose of protection is to ensure the full rights of children to live, grow and participate optimally in accordance with human dignity and dignity, and to be protected from violence and discrimination, in order to realize quality Indonesian children who are noble and prosperous. Criminal action is a term commonly used in Indonesian law, where the term criminal act emphasizes an action that includes the meaning of doing or acting actively and not doing passively which is closely related to an attitude of someone who acts or acts. The actions or actions referred to contain elements or unlawful nature of an existing legal rule that prohibits such actions so that these actions can be punished.